Adaptation of Music Therapists' Practice to the Outset of the COVID-19 Pandemic-Going Virtual: A Scoping Review - Kantorová, Lucia; Kantor, Jiří; Hořejší, Barbora; Gilboa, Avi; Svobodová, Zuzana; Lipský, Matěj; Marečková, Jana; Klugar, Miloslav (International journal of environmental research and public health, 2021)
Background: In the midst of a worldwide COVID-19 pandemic, music therapists previously not involved in telehealth had to develop effective remote forms of music therapy. The objective of this review was to systematically explore how music therapists previously working in-person adapted to the transfer to remote forms of therapy in the context of the coronavirus outbreak. Methods: We searched Scopus, Web of Science Core Collection, CINAHL, Medline, ProQuest Central, PubMed, EMBASE, PsycINFO and PsyARTICLES, grey literature (to October 2020), and websites of professional organizations. We followed the JBI methodology for scoping reviews. Results: Out of the 194 screened texts, we included ten very heterogeneous articles with an overall very low quality. Most texts described remote therapy in the form of synchronous video calls using the Internet, one paper described a concert in a patio of a residential home. We report the authors' experience with the adaptation and activities, challenges and benefits of remote forms of therapy, recommendations of organizations, and examples and tips for online therapies. Conclusions: Music therapists have adapted the musical instruments, the hours, the technology used, the therapeutic goals, the way they prepared their clients for sessions, and other aspects. They needed to be more flexible, consult with colleagues more often, and mind the client-therapist relationship's boundaries. It seems, when taken as a necessary short-term measure, online music therapy works sufficiently well. The majority of papers stated that benefits outweighed the challenges, although many benefits were directly linked with the pandemic context.
Keywords: pandemie; lidé; Telemedicine; SARS-CoV-2; Music; Pandemics; telemedicína; COVID-19; hudba; Humans